Omani hydrogen for Germany and the EU: Not just a matter of energy policy - Dawud Ansari (Stiftung Wissenschaft und Politik (SWP), 2023)
Germany and the EU plan to import hydrogen and its derivatives from the Arab Gulf states. Although Germany has signed a joint declaration of intent with the Sultanate of Oman to this end, its efforts focus primarily on Oman's larger neighbours. However, it would be a mistake to overlook Oman's potential role within German and European energy policy, geostrategy, and climate diplomacy. Oman's ambitious hydrogen plans can provide Germany and the EU with affordable clean energy; and enhanced (trade) relations with the Sultanate align with a value-based approach to trade, support global climate action, and stabilise regional power balances - thus preventing the potential of dangerous conflict.
Keywords: 320; Germany; EU; hydrogen imports; Oman; United Arab Emirates (UAE); Yemen; Saudi Arabia; Qatar; Kuwait; liquefied natural gas (LNG)